Presurgical Orthodontic Decompensation of Mandibular Incisors - Xu Baohua; Ju Zeching; Hagg Urban; Tideman Henk; Piette Etienne (Sciendo, 1995)
The effects of presurgical orthodontic decompensation on lower incisor inclination und angle ANB were studied using u modified Pancherz10 method of cephalometric analysis. Two groups of patients with mandibular hyperplasia were studied: one group (Group 1) of nineteen cases which required orthodontic decompansation and another (Group 2) of twenty-one cases which did not. The cephalometric changes wluch occurred in Group 1 were compared with the significant cephalometric differences existing between the two groups with respect to incisor inclination (ILi/OL; P<.001) and the sagittal relation (ANB; P<0.05). After orthodontic treatment the average lower incisal angulation of the treated group was the same as that in the untreated group; the variations (S.D) being 3.6 degrees and 7.4 degrees respectively indicating that the clinical assessment of the orthodontic treatment effect was quite high.